Pemanfaatan Limbah Ampas Kopi Dalam Pembuatan Sabun Batang di Kampung Wisata Kopi Lerek Gombengsari Banyuwangi - Ayu Purwaningtyas; Aprilia Divi Yustita; Sari Wiji Utami (Universitas Lancang Kuning, 2022)
Lerek Gombengsari (Lego) Coffee Tourism Village is one of the coffee educational tourism destinations in Banyuwangi. This tourist destination combines agro-tourism and educational tourism so that visitors can learn and practice coffee plantation management organically with an educational system adhering to the principle of Learning by doing. The use of coffee in the Gombengsari area is still limited to coffee beans. Coffee beans are processed into coffee grounds which are enjoyed by tourists, both domestic and foreign tourists. The processing of coffee beans produces 45% of coffee waste in the form of coffee grounds and each cup of coffee drunk containing coffee grounds has an average weight of 20 grams. Therefore, coffee grounds waste must be processed because it can be harmful to health and the environment. Coffee grounds waste contains caffeine, organic acids, minerals and antioxidants that are useful for smoothing the skin, moisturizing the skin and preventing free radicals. Based on these contents, the coffee grounds at Kampung Lego Tourism will be processed into traditional soap bars. Making bar soap is done traditionally to avoid chemicals so that it can reduce problems on the skin. The PKM activity by the Poliwangi Lecturer Team was able to produce processed bar soap products which were packaged under the name Srikandi Homemade Soap. These results are able to add to the list of processed variants that are very useful for partners.